Readiness to Implement Smart Logistics from an International Perspective : A Review - Aulia Zikri Rahman; Vina Dwiyanti; Akhsin Nurlayli (Universitas Pendidikan Indonesia, 2021)
Modern logistics technology may be the key to breaking the deadlock. Utilizing modern logistics technology to build an efficient logistics platform is an effective way to capture opportunities in today's global competitive environment. However, modern logistics still encounter several challenges. Fortunately, the development of big data and smart technology has driven the development of smart logistics. Building a smart logistics platform is conducive to controlling costs, increasing efficiency, reducing energy consumption, etc. With advances in information technology, the existing modern logistics technology can be enhanced to produce maximum and measurable output. This paper aims to discuss findings about the extent to which artificial intelligence is applied in supporting logistical activities by targeting several previous studies. The following literature study aims to determine the level of usability that has been applied in the implementation stage. In order to obtain data or information, proposers conduct a review of previous studies. This literature study was carried out with the aim of seeing the level of satisfaction and usability of the use of Artificial Intelligence in the logistics sector from the stakeholder's point of view. The information obtained in the discussion section shows that use shows a significant impact on indicators of effectiveness, efficiency, and productivity levels.